The Relationship Between the Visionary Hero and Compensation on Employee Performance Effectiveness - Kiemas Kurniawan; Herlin (Kusuma Negara Business School, 2022)
This study aims to determine the relationship between The Visionary Hero, compensation, and the effectiveness of employee performance at BPBD Rejang Lebong. The sample of this research is 36 respondents and the analytical method used is Spearman rank correlation analysis and t test. The results of the calculation of the variable the visionary hero with Spearman rank correlation value of 0.436 lies between 0.40-0.599 meaning that it has a moderate level of relationship, which is strengthened by the results of hypothesis testing where t statistic > t table (2.8247 < 2.0345), thus H0 rejected Ha accepted, meaning that there is a significant relationship between leadership style and the performance of BPBD Rejang Lebong employees. The results of the calculation of the compensation variable with the Spearman rank correlation obtained that the value of 0.648 lies between 0.60-0.799, meaning that it has a strong relationship level and is strengthened by the results of hypothesis testing, where t statistic > t table (4.9613 < 2.0345), which means that there is a significant relationship between compensation and the effectiveness of the performance of BPBD Rejang Lebong employees.